MORPHOLOGICAL CHARACTERISTICS AND POLLINIA OBSERVATION OF 10 INDONESIA NATIVE DENDROBIUM ORCHIDS - Indraloka, Aldy Bahaduri; Dewanti, Parawita; Restanto, Didik Pudji (BIOVALENTIA: Biological Research Journal, 2019)
Characterization of native orchid (species) in Indonesia is important for preservation of germplasm and selection process to obtain dominant character of orchids as potential parental. Morphological characterization is a method to obtain scientific information in phenotypic manner. Characterization of plants was carried out on 10 native orchids of Dendrobium genus to obtain specific character. Characterization process based on UPOV guidebook and morphological observation of pollinia was also carried out on 10 native orchids to obtain information about the structure and physiology of pollinia. The results of morphological characterization on 10 native orchid showed several qualitative characters such as flowering position, cross section of leaf, pseudobulb firmness, and leaf arrangement in D. Canaliculatum was different from 9 other native orchid. Morphological pollen of 10 native orchid shows the diversity structure of pollinia and the physiological conditions of mature pollen which are ready to pollinate are pollinia with a golden yellow colored. Knowledge and information about parental relationships is the main point for developing ornamental plant breeding programs. Selection of native orchids as potential elder is important where selected elders will be used as a source of genetic diversity. The results of this study are expected to provide scientific information and phenotypic selection for the development of hybrid orchids.